A new genus and species of Chamaemyiidae (Diptera: Lauxanioidea) from South America feeding on Ceroplastes wax scales (Hemiptera: Coccidae), and status of the genus Ortalidina as a chamaemyiid - Gaimari, Stephen D. (Zootaxa, 2012)
A new genus and species of Chamaemyiidae (Diptera: Lauxanioidea) is described and illustrated, namelyChamaeleucopis, gen. nov. (type species Chamaeleucopis trevas, sp. nov.), a predator of Ceroplastes wax scales on guavafrom Brazil. In addition, the previously unrecognized genus Ortalidina Blanchard 1852 (type species Ortalidina cellularisBlanchard 1852), mainly from the Neotropics, is recognized as a chamaemyiid, and is the senior synonym of ToropameciaCogan 1978, syn. nov. (type species Acrometopia punctata Coquillett 1902). The species Toropamecia grossa Cogan1978, syn. nov., is synonymized under Ortalidina cellularis. All species therein become new combinations withinOrtalidina, including (in their original combinations) Acrometopa australis Malloch 1933, comb. nov., Acrometopiamaculata Coquillett 1902, comb. nov., Acrometopia punctata Coquillett, comb. nov., Toropamecia apaxa Cogan 1978,comb. nov., Toropamecia caribbea Cogan 1978, comb. nov., Toropamecia hendeli Cogan 1978, comb. nov., Toropameciahyalipennis Cogan 1978, comb. nov., Toropamecia jujuyensis Cogan 1978, comb. nov., Toropamecia longipennis Cogan1978, comb. nov., Toropamecia macalpinei Cogan 1978, comb. nov., Toropamecia multipunctata Cogan 1978, comb. nov.,Toropamecia nigripalpis Cogan 1978, comb. nov., Toropamecia reducta Cogan 1978, comb. nov., Toropamecia smithiCogan 1978, comb. nov., Toropamecia veenota Cogan 1978, comb. nov., Trigonometopus reticulatus Johnson 1913, comb. nov. A habitus photo of the primary type for each species of Ortalidina is provided.